The Phenomenon Of Bullying Among Teenagers In A Thematic Hadith Perspective - Khania Salsabila; Salim Rosyadi (International Journal of Social Science and Humanity, 2024)
Bullying has serious and long-term effects on adolescents. Victims of bullying have a higher risk of experiencing physical and psychosomatic problems such as headaches, stomachaches, and sleep problems. They are also at higher risk of internalizing problems such as anxiety and depression in young adulthood and middle adulthood. Bullying can also have a negative impact on both the victim and the bully. It can lead to physical injury, social and emotional distress, self-harm, and even death. Teens who bully others have a higher risk of drug abuse, academic problems, and experiencing violence in adolescence and adulthood. The issue of bullying becomes a big problem if it is not addressed. It is important to prevent bullying and provide support to those who are victims. The object of this research material is a case of bullying according to the hadith themes. This study uses a qualitative approach by applying the thematic method. The results of this study show that the themes of hadith can be formulated in the theoretical framework of the phenomenon of bullying in adolescents. The discussion of this study explains that bullying is not relevant to the teachings of Islam